Polyacrylonitrile/noble metal/SiO2 nanofibers as substrates for the amplified detection of picomolar amounts of metal ions through plasmon-enhanced fluorescence. Issue 4 (10th December 2014) - Zhang, Han; Cao, Minhua; Wu, Wei; Xu, Haibo; Cheng, Si; Fan, Li-Juan
Abstract : A general approach is proposed for the first time for plasmon-enhanced fluorescence-active PAN/noble metal/SiO2 nanofibrous mats with a greatly improved detection sensitivity for picomolar amounts of metal ions. Abstract : Electrospun polymer/noble metal hybrid nanofibers have developed rapidly as surface-enhanced Raman scattering (SERS)-active substrates over the last few years. However, polymer/noble metal nanofibers with plasmon-enhanced fluorescence (PEF) activity have received no attention to date. Herein, we show a general and facile approach for the preparation of polyacrylonitrile (PAN)/noble metal/SiO2 nanofibrous mats with PEF activity for the first time by combining electrospinning and controlled silica coatings. These PEF-active nanofibrous mats can selectively improve the fluorescence intensity of conjugated polyelectrolytes (CPEs). Importantly, the CPE solution in the presence of a PAN/noble metal/SiO2 nanofibrous mat showed dramatic fluorescence quenching towards picomolar (pM) amounts of heavy metal ions, while the fluorescence of the CPE solution without the nanofibrous mat had no apparent quenching towards micromolar (μM) amounts of metal ions. The combination of the distance-dependent fluorescence enhancement performance of metal NPs and the ionic characteristics of the CPE solution makes the polymer/noble metal nanofibers promising substrates for greatly improving the detection sensitivity towards metal ions. We believe that this work provides a general strategy for preparing plasmon band-tuned PEF-active substrates with advantages including good selectivity, remarkable sensitivity and recyclability, which make them a preferable choice for practical sensing applications.